AN ANALYSIS OF CONTENT VALIDITY OF THE TEST - Erlik Widiyani Styati (Universitas PGRI Madiun, 2013)
Analyzing the result of the learners in a foreign language is needed. Besides, many teachers still find difficulty in analyzing the test item. It is used to know the achievement of the learners. Otherwise, the teachers also still find difficulty in giving the mark. It is meant that they lack to recognize whether the learners are in a good achievement. Furthermore, the paper aims to describe how to analyze the content validity of the test item. Analyzing content validity is the way to know whether the test is appropriate with the curriculum or not.